Self Directed Work Team’s Effectiveness - QUAH, EE BOON (2005)
The use of Self Directed Work Team in manufacturing organizations has increased in response to competitive challenges. The present study attempts to provide empirical evidence on the relationship between Team Characteristics (Team Composition, Team Beliefs, Team Process and Team Stability), Team Task Design and Team Task Meaningfulness with Self Directed Work Team’s effectiveness (Self Directed Work Team’s performance and the team member’s Quality of Work Life). It also explores whether Availability of Resources and Measure of Team Performance and Rewards moderate the said relationships.